2019
DOI: 10.1021/acsaem.9b02014
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Copper Separation in Lithiated Cu6Sn5 Lithium-Ion Battery Anodes

Abstract: Intermetallics such as Cu6Sn5, NiSi2, and CuGa2 etc., are promising candidate materials to replace carbon-based lithium-ion battery anodes. However, the lithiation reactions of these anodes often involve the separation of the inactive phases, a slow process that retards the lithiation kinetics and deactivates their role as a stress buffer. This research visualizes the separated Cu in a lithiated Cu6Sn5 anode by advanced transmission electron microscopy techniques. Cu nanospheres of 3–4 nm are found homogeneous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 20 publications
2
16
0
Order By: Relevance
“…The sample was then cooled to room temperature in air, mounted in epoxy resin and polished with standard metallography procedures to expose the cross-sectioned microstructure. A TEM lamellar of approximately 16 µm × 25 µm was prepared using a focused ion beam (FIB) technique on a FEI Scios FIB-dual beam scanning electron microscope (SEM), similar to a technique described elsewhere [20]. The sample was extracted from a region of interest (ROI) at the Cu/IMCs/SAC interface (Figure 1a) and welded to a Cu TEM half grid by Pt deposition.…”
Section: Methodsmentioning
confidence: 99%
“…The sample was then cooled to room temperature in air, mounted in epoxy resin and polished with standard metallography procedures to expose the cross-sectioned microstructure. A TEM lamellar of approximately 16 µm × 25 µm was prepared using a focused ion beam (FIB) technique on a FEI Scios FIB-dual beam scanning electron microscope (SEM), similar to a technique described elsewhere [20]. The sample was extracted from a region of interest (ROI) at the Cu/IMCs/SAC interface (Figure 1a) and welded to a Cu TEM half grid by Pt deposition.…”
Section: Methodsmentioning
confidence: 99%
“…The lithiation and delithiation voltages of the electrodes, where V L1peak and V L2peak are the peak lithiation voltages for the first and second lithiation reaction respectively; V L2onset is the onset voltage for the second lithiation reaction; and V D1peak and V D2peak are the peak lithiation voltages during the first and second delithiation reaction, respectively this reaction is often not completed even when the system is lithiated to 0 V versus Li/Li + , therefore, in practice, the final product of Sn-based anodes are often Li 7 Sn 2 instead of the theoretical Li 22 Sn 5 . [38] In the case of the electrode fabricated with this method, spherical aberration corrected scanning transmission electron microscopy (C s -corrected STEM) [39] and in situ synchrotron powder X-ray diffraction (PXRD) [16] showed that the reactant in the second lithiation reaction described in Equation ( 2), Li 13 Cu 6 Sn 5 , and the products, Li (13+y) Sn 5 and Cu are present upon lithiation to 0.02 V, that is, the second lithiation reaction only proceeds partially. The increase in voltage during the second lithiation reaction of Cu 6 Sn 5 -lCo helps in achieving a deeper lithiation, thereby increasing the capacity of the electrodes as seen in the rate capability and the 50-cycle tests.…”
Section: Ta B L Ementioning
confidence: 99%
“…The TEM lamellar was prepared by a focused ion-beam (FIB) technique described elsewhere [17], and thinned by an ion mill at 900 eV to a thickness of about 50 nm for electron transparency, before imaging and EDS in a C s -corrected STEM at 200 kV accelerating voltage. The TEM selected area electron diffraction (SAED) patterns were also obtained.…”
Section: Materials Characterisationmentioning
confidence: 99%